Maps and digital technologies: new literacies on the agenda of geography teaching - Tânia Seneme do Canto (Universidade Federal de Santa Catarina, 2018)
Taking as a reference the discussion about new literacies and digital technologies, this article addresses the new possibilities and needs that mapping practices developed under contemporary technological conditions raise for the teaching of geography. As will be noted, digital technologies have allowed the emergence of forms of production and use of maps that differ significantly from other pre-existing ones. Marked by the modes of communication and interaction of a new culture, this new cartography carries with it the possibility of literacy practices quite different from others with great tradition in school geography and cartography. Thus, the ruptures and knowledge that new cartographic literacies make possible and require in geography teaching are the main questions that guide this text.